Simple profits from swing trading, revised and updated : the underground trader swing trading system explained - Yu, Jea (Wiley, 2014)
There are so many trading systems out there today, each one claiming to have the secret that will bring windfall returns. Some may fare well in rising markets, but all too often leave the trader struggling to keep their head--and capital--up when the market starts to fall. Doesn't sound too reliable, does it? The Underground Trader Swing Trading system is unlike any other. Having been meticulously forged by hand from hours of active market participation and analysis from over a decade, it is an all-encompassing system that performs strong when the market is rising and perhaps even.